Obtenção de correlações para a estimativa do coeficiente convectivo de transferência de massa para geometria esférica a partir da técnica de sublimação do naftaleno - Moreira, Bruno Arantes (2010)
Many industrial processes involve the knowledge of heat and mass transfer rates for a fluid passing through solid objects. These rates are functions of parameters called convective heat transfer coefficient (h), for situations involving the transport of energy and convective mass transfer coefficient (km) for situations involving the transport of matter. These coefficients are related with the influences of hydrodynamic nature, geometry and molecular interactions and despite its relative complexity, correlation using dimensionless numbers estimate these parameters with good confidence. One method that has been used to obtain the heat transfer coefficient (h) is to conduct experiments of mass transfer that are easier to be realized and have higher accuracy in measurements. The results of mass transfer can be validated for heat transfer by simple analogy between the phenomena. In this context, convective mass transfer correlations for single geometries (spheres, cylinders and flat plat) have been widely used to estimate values of convective heat and mass transfer coefficient (h, km). In this study correlation of mass transfer for single spheres was proposed included in the rage of 180≤Rep≤5000. The values of km were obtained using naphthalene spheres under different conditions of air flow. The results obtained showed a good agreement when compared with other correlations in the literature. Nevertheless, the naphthalene sublimation technique was investigated as a method for obtaining convective coefficients, showing to be satisfactory in the study of heat and mass transfer.